Inflammatory markers in depression: A meta-analysis of mean differences and variability in 5,166 patients and 5,083 controls - Osimo, Emanuele F.; Pillinger, Toby; Rodriguez, Irene Mateos; Khandaker, Golam M.; Pariante, Carmine M.; Howes, Oliver D. (Brain, behavior, and immunity, 2020)
•Patients with depression show reduced variability in pro-inflammatory immune measures.•Patients with depression show increases in pro-inflammatory immune markers mean levels, and reductions in anti-inflammatory IL-4. The magnitude and variability of cytokine alterations in depression are not clear. To perform an up to date meta-analysis of mean differences of immune markers in depression, and to quantify and test for evidence of heterogeneity in immune markers in depression by conducting a meta-analysis of variability to ascertain whether only a sub-group of patients with depression show evidence of inflammation. Studies that reported immune marker levels in peripheral blood in patients with depression and matched healthy controls in the MEDLINE database from inception to August 29th 2018 were examined. Case-control studies that reported immune marker levels in peripheral blood in patients with depression and healthy controls were selected. Means and variances (SDs) were extracted for each measure to calculate effect sizes, which were combined using multivariate meta-analysis. Hedges g was used to quantify mean differences. Relative variability of immune marker measurements in patients compared with control groups as indexed by the coefficient of variation ratio (CVR). A total of 107 studies that reported measurements from 5,166 patients with depression and 5,083 controls were included in the analyses. Levels of CRP (g = 0.71; 95%CI: 0.50–0.92; p < 0.0001); IL-3 (g = 0.60; 95%CI: 0.31–0.89; p < 0.0001); IL-6 (g = 0.61; 95%CI: 0.39–0.82; p < 0.0001); IL-12 (g = 1.18; 95%CI: 0.74–1.62; p < 0.0001); IL-18 (g = 1.97; 95%CI: 1.00–2.95; p < 0.0001); sIL-2R (g = 0.71; 95%CI: 0.44–0.98; p < 0.0001); and TNFα (g = 0.54; 95%CI: 0.32–0.76; p < 0.0001) were significantly higher in patients with depression. These findings were robust to a range of potential confounds and moderators. Mean-scaled variability, measured as CVR, was significantly lower in patients with depression for CRP (CVR = 0.85; 95%CI: 0.75–0.98; p = 0.02); IL-12 (CVR = 0.61; 95%CI: 0.46–0.80; p < 0.01); and sIL-2R (CVR = 0.85; 95%CI: 0.73–0.99; p = 0.04), while it was unchanged for IL-3, IL-6, IL-18, and TNF α. Depression is confirmed as a pro-inflammatory state. Some of the inflammatory markers elevated in depression, including CRP and IL-12, show reduced variability in patients with depression, therefore supporting greater homogeneity in terms of an inflammatory phenotype in depression. Some inflammatory marker elevations in depression do not appear due to an inflamed sub-group, but rather to a right shift of the immune marker distribution.